URANIUM CO-PRECIPITATION WITH IRON OXIDE MINERALS - Duff M.C.; Coughlin J.U.; Hunter D.B. (My University, 2002)
In oxidizing environments, the toxic and radioactive element uranium (U) is most soluble and mobile in the hexavalent oxidation state. Sorption of U(VI) on Fe-oxides minerals (such as hematite [α-Fe2O3] and goethite [α-FeOOH]) and occlusion of U(VI) by Fe-oxide coatings are processes that can retard U transport in environments. In aged U-contaminated geologic materials, the transport and the biological availability of U toward reduction may be limited by coprecipitation with Fe-oxide minerals. These processes also affect the biological availability of U(VI) species toward reduction and precipitation as the less soluble U(IV) species by metal-reducing bacteria.To examine the dynamics of interactions between U(VI) and Fe oxides during crystallization, Fe-oxide phases (containing 0.5 to 5.4 mol% U/(U + Fe)) were synthesized by means of solutions of U(VI) and Fe(III). Wet chemical (digestions and chemical extractions) and spectroscopic techniques were used to characterize the synthesized Fe oxide coprecipitates after rinsing in deionized water. Leaching the high mol% U solids with concentrated carbonate solution (for sorbed and solid-phase U(VI) species) typically removed most of the U, leaving, on average, about 0.6 mol% U. Oxalate leaching of solids with low mol% U contents (about 1 mol% U or less) indicated that almost all of the Fe in these solids was crystalline and that most of the U was associated with these crystalline Fe oxides. X-ray diffraction and Fourier-transform infrared (FT-IR) spectroscopic studies indicate that hematite formation is preferred over that of goethite when the amount of U in the Fe-oxides exceeds 1 mol% U (~4 wt% U). FT-IR and room temperature continuous wave luminescence spectroscopic studies with unleached U/Fe solids indicate a relationship between the mol% U in the Fe oxide and the intensity or existence of the spectra features that can be assigned to UO22+ species (such as the IR asymmetric υ3 stretch for O = U = O for uranyl). These spectral features were undetectable in carbonate- or oxalate-leached solids, suggesting solid phase and sorbed U(VI)O22+ species are extracted by the leach solutions. Uranium L3-edge x-ray absorption spectroscopic (XAFS) analyses of the unleached U-Fe oxide solids with less than 1 mol% U reveal that U(VI) exists with four O atoms at radial distances of 2.19 and 2.36 Α and second shell Fe at a radial distance at 3.19 Α.Because of the large ionic radius of UO22+ (~1.8 Α) relative to that of Fe3+ (0.65 Α), the UO22+ ion is unlikely to be incorporated in the place of Fe in Fe(III)-oxide structures. Solid-phase U(VI) can exist as the uranyl [U(VI)O22+] species with two axial U-O double bonds and four or more equatorial U-O bonds or as the uranate species (such as γ-UO3) without axial U-O bonds. Our findings indicate U6+ (with ionic radii of 0.72 to 0.8 Α, depending on the coordination environment) is incorporated in the Fe oxides as uranate (without axial O atoms) until a point of saturation is reached. Beyond this excess in U concentration, precipitating U(VI) forms discrete crystalline uranyl phases that resemble the uranyl oxide hydrate schoepite [UO2(OH)2.2H2O]. Molecular modeling studies reveal that U6+ species could bond with O atoms from distorted Fe octahedra in the hematite structure with an environment that is consistent with the results of the XAFS. The results provide compelling evidence of U incorporation within the hematite structure.